1370-P: Pregnant Dyslipidemia Affects Postpartum Metabolism in Gestational Diabetes Mellitus Patients - XIAO, HUANGMENG; PEI, LING; LI, ZETING; HUANG, XIAOYU; YUE, SHUFAN; CAO, XIAOPEI (Diabetes (New York, N.Y.), 2020)
Women with gestational diabetes mellitus (GDM) have higher rate of dyslipidemia during pregnancy than those without GDM. However, whether this higher level of blood lipid during pregnancy in GDM women has effects on postpartum metabolism is rarely reported. The purpose of this study is to assess the influence of dyslipidemia during pregnancy on postpartum metabolism in women with history of GDM . A total of 443 women with history of GDM were enrolled in this retrospective cohort study. All of them have completed revisit at 4-12 week postpartum. The demographic and pregnant medical records were collected. In the postpartum revisit, 75g-OGTT test and physical examination were performed. The serum lipid level and insulin concentration were measured. Pregnant dyslipidemia were categorized according to the criteria of Williams obstetrics in pregnancy. The relationship between pregnant dyslipidemia and postpartum metabolism was statistically analyzed. On the whole, postpartum blood lipid levels showed a downward trend comparing with those during pregnancy. However, 39.4% of those GDM women presented dyslipidemia at 4-12 week postpartum, including 61.2% of mixed hyperlipidemia, and 38.8% of single component dyslipidemia. Women with pregnant dyslipidemia had higher postpartum total cholesterol level, TG level as well as LDL-c level. The triglyceride (TG) level during pregnancy were positively correlated with postpartum fasting blood glucose level, fasting insulin level and insulin resistance index (HOMA-IR). On the other hand, the HDL-c level during pregnancy were negatively correlated with postpartum fasting blood glucose and HOMA-IR. In conclusion, the abnormally increased blood lipid levels during pregnancy in GDM women are relative to the postpartum hyperglycemia and hyperlipidemia. Management of pregnant dyslipidemia may be beneficial to the postpartum metabolism in GDM women.